Management and utilization of seals in Greenland, February 2015. Addendum to: White Paper on Management and Utilization of Seals in Greenland (April 2012). : Updated data to: Management and utilization of seals in Greenland. Addendum to: White Paper on Management and Utilization of Seals in Greenland (April 2012) - Unkn Unknown (Government of Greenland, Department of Fisheries, Hunting & Agriculture, 2015)
This document is an addendum to the White Paper on Management and Utilization of Seals in Greenland from April 2012 and the two documents should be read together. Box 1: Abundant seal populations Harp seal: Advice on sustainable use on harp seal is given by a working group under the International Council for the Exploration of the Sea (ICES/NAFO: WGHARP). The working group consists of scientist from Norway, Canada, Greenland and Russia. Roughly every fifth year the pup production is estimated by surveys. The total number of seals in the stock is then calculated based on the survey estimate and data on the age-distribution in the stock, age of sexual maturity, the reproduction rate of the adult females and data on the catches. In many years the working group calculated quotas small enough to allow the stocks to grow. This led to a steady growth in periods when the quotas were taken and strong growth in periods with small commercial catches. The stock that give birth in the Greenland Sea seem to continue its growth, but the west Atlantic population that whelp around Newfoundland now seem to have reached the carrying capacity of its habitat. This means that the fecundity of the seals has been significantly reduced, so that the population no longer produces a surplus every year. New management principles, which allow a reduction of the seal populations has therefore been introduced. The reduction is limited to a magnitude that secures a large and healthy population, which will produce up to the maximum sustainable yield (MSY) of the population. A population around the carrying capacity produce no surplus (pup production roughly equals natural mortality). A surplus is created and increase as the population is reduced down to a point with the maximum sustainable yield. For harp seals this is a point (believed to be around 70% of the carrying capacity level), when both the population and the reproduction is high. The new management principles allow a reduction of the populations to 70% of their maximum levels. Quotas can therefore be set based on ecological or socioeconomic considerations as long as the population is kept above 70% of Nmax, which for the West Atlantic population has been set to 7.8 million - the level found in 2008. If the stock gets below 70 %, of the maximal size, a management plan should be initiated with the purpose of increasing the stock above 70 % again. If the stock gets below 50 %, further protection measures should be initiated, and if the stock gets below 30 % all hunting should be stopped. This type of management should only be used for stocks with reliable and plenty data. ICES/NAFO working group on harp and hooded seals estimated the population in the Northwest Atlantic to be approximately 7.4 million seals in 2014. This is a reduction of 400,000 seals since 2008, but this reduction has mainly been caused by low reproduction and high natural mortality (many pups dying in years with poor ice conditions in the whelping areas). The total allowable catch (TAC) for Canada is set to 400,000 (since 2011). , but catches in Canada has since 2008 been far below the TAC. In 2013, Greenland caught about 79,600 harp seals while Canada caught about 94,000 harp seals, less than 44 % of the TAC. Ringed seal: In 1996 a working group established by The North Atlantic Marine Mammal Commission’s (NAMMCO) Scientific Committee concluded that Greenland’s current take of ringed seal was sustainable. Three substantial arguments for this conclusion were that the current hunting pressure has been maintained for a number of years without visible signs of a decline in the population, that Greenland’s take is particularly made up of males and very young individuals and that the ringed seal’s very wide and even distribution across most of the Arctic limits large-scale overexploitation. Even though ringed seals are widely dispersed and apparently capable of surviving under very severe ice conditions, they are considered vulnerable to sudden changes in ice coverage. 4 Box 1: continued The total number of ringed seals is still unknown, but is estimated to 6-7 million. Among them, approx. 1 million are of the subspecies Pusa hispida ochotensis, while the other three southern subspecies together only constitute in the region of 10,000 individuals. The estimate of Arctic ringed seals is about 5 million. Hooded seal: ICES/NAFO working group on harp and hooded seals estimates the current population in the Northwest Atlantic at 600,000 seals in 2005 (last assessment), which is an increase from 478,000 in 1965. In Canada the TAC on hooded seals older than bluebacks has been at 8,200 seals since 2008. It is, however, mainly the blue back skin that is of interest for the sealers and in recent years less than hundred hooded seals have been caught annually in Canada. No hooded seals were reported taken in 2013 and according to the preliminary estimates for 2014 only 7 hooded seal was taken. In 2013, Greenland caught 1,498 hooded seals, which is the lowest catch since 1962. The population is not considered endangered. The Greenland Sea stock of hooded seal was severely overexploited by Norwegian sealers in the years after the Second World War. It is presently at a level around 80,000, which is believed to be less than 30 % of former levels and all commercial hunting has stopped. Since 2007 only few seals have been taken for scientific purposes and a small insignificant number (since 2006 less than 10/yr.) is taken by hunters from the Greenland settlement Ittoqqortoormiit